Strategic Model for Strengthening Digital Literacy at UIN Ponorogo And UIN Kediri: Synergy of Curriculum and Educational Programs - Supriati, Eny; Antikasari, Tiara Widya; Komarudin (MUSLIM HERITAGE, 2025)
Abstract The rapid development of information requires synergy between the curriculum, the academic community, and institutional policies so that digital literacy is not only a technical skill, but also integrated with Islamic values, learning processes, and academic culture. This study aims to examine the strategy of strengthening digital literacy at the Ponorogo State Islamic University and Kediri through a collaborative approach to improve students' digital literacy competencies. Using qualitative descriptive methods with a comparative approach, through participatory observation, in-depth interviews, and documentation analysis. The results of the study show that the strategy of strengthening digital literacy in both institutions adopts the theory of Norhasni Zainal Abiddin, Gillian Hallam, and Maria Spante, which includes cognitive, emotional, and social aspects. UIN Ponorogo emphasizes strengthening the competence of reference management, technological understanding, and social interaction through social media promotion, as well as literacy class programs and special training for final year students. Meanwhile, UIN Kediri focuses on strengthening digital literacy strategies on improving scientific and popular article writing skills, as well as the use of the Maktabah Syamilah application for hadith search, which is realized through synergy between libraries and faculties. Both institutions showed significant progress in students' digital literacy, although they still faced challenges such as limited infrastructure and the absence of written institutional policies. As a recommendation, this study proposes the integration of digital literacy into the core curriculum, the implementation of periodic evaluations, adequate budget allocation, and the strengthening of infrastructure.   Abstrak Pesatnya perkembangan informasi menuntut sinergi antara kurikulum, sivitas akademika, dan kebijakan institusi agar literasi digital tidak hanya menjadi keterampilan teknis, tetapi juga terintegrasi dengan nilai-nilai keislaman, proses pembelajaran, dan budaya akademik. Penelitian ini bertujuan mengkaji strategi penguatan literasi digital di Universitas Islam Negeri Ponorogo dan Kediri melalui pendekatan kolaboratif guna meningkatkan kompetensi literasi digital mahasiswa. Menggunakan metode deskriptif kualitatif dengan pendekatan komparatif, melalui observasi partisipatif, wawancara mendalam, dan analisis dokumentasi. Hasil penelitian menunjukkan bahwa strategi penguatan literasi digital di kedua institusi mengadopsi teori Norhasni Zainal Abiddin, Gillian Hallam, dan Maria Spante, yang mencakup aspek kognitif, emosional, dan sosial. UIN Ponorogo menitikberatkan penguatan kompetensi manajemen referensi, pemahaman teknologi, dan interaksi sosial melalui promosi media sosial, serta program kelas literasi dan pelatihan khusus bagi mahasiswa tingkat akhir. Sementara itu, UIN Kediri memfokuskan strategi penguatan literasi digital pada peningkatan keterampilan penulisan artikel ilmiah dan populer, serta pemanfaatan aplikasi Maktabah Syamilah untuk penelusuran hadis, yang diwujudkan melalui sinergi antara perpustakaan dan fakultas. Kedua institusi menunjukkan perkembangan signifikan dalam literasi digital mahasiswa, meskipun masih menghadapi tantangan seperti keterbatasan infrastruktur dan belum adanya kebijakan institusional yang tertulis. Sebagai rekomendasi, penelitian ini mengusulkan integrasi literasi digital ke dalam kurikulum inti, pelaksanaan evaluasi berkala, alokasi anggaran yang memadai, serta penguatan infrastruktur.